2013
DOI: 10.1038/emm.2013.93
|View full text |Cite
|
Sign up to set email alerts
|

Contralaterally transplanted human embryonic stem cell-derived neural precursor cells (ENStem-A) migrate and improve brain functions in stroke-damaged rats

Abstract: The transplantation of neural precursor cells (NPCs) is known to be a promising approach to ameliorating behavioral deficits after stroke in a rodent model of middle cerebral artery occlusion (MCAo). Previous studies have shown that transplanted NPCs migrate toward the infarct region, survive and differentiate into mature neurons to some extent. However, the spatiotemporal dynamics of NPC migration following transplantation into stroke animals have yet to be elucidated. In this study, we investigated the fates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…This NSC line is well characterized: it expresses the NSC-specific markers nestin and SOX2 and differentiates into neurons, oligodendrocytes, and astrocytes (21). H9 NSCs were trans duced to express GFP and were harvested and embedded in fibrin matrices containing a growth factor cocktail (see Methods and ref.…”
Section: Resultsmentioning
confidence: 99%
“…This NSC line is well characterized: it expresses the NSC-specific markers nestin and SOX2 and differentiates into neurons, oligodendrocytes, and astrocytes (21). H9 NSCs were trans duced to express GFP and were harvested and embedded in fibrin matrices containing a growth factor cocktail (see Methods and ref.…”
Section: Resultsmentioning
confidence: 99%
“…MSCs from cord blood, bone marrow and adipose decrease TUNELlabeled neurons, decrease caspase 3 mRNA, increase Bcl-2 expression (Calio et al, 2014; Feng et al, 2016; Li et al, 2002; Liu et al, 2014; Wu et al, 2008; Zhu et al, 2014). NSCs have similar effects when transplanted into the cortical peri-infarct area 24 h after permanent MCAO (Chen et al, 2014; Zhang et al, 2009) or even when administered one week after MCAO (Chang et al, 2013b; Shen et al, 2010. Even NSCs derived from iPSCs can decrease apoptosis (Chang et al, 2013a; Yao et al, 2015).…”
Section: Putative Therapies For Enhancing Brain Self-repair and Strokmentioning
confidence: 99%
“…multi-lineage differentiation). Regarding the use of stems cells in the treatment of stroke, experimental studies using embryonic stem cells (Chang et al 2013;Drury-Stewart et al 2013), mesenchymal stem cells (Ikegame et al 2011), hematopoietic stem cells (Tsuji et al 2014), neural stem cells (Andres et al 2011), induced pluripotent stem cells (iPSC) (Oki et al 2012), and also multipotent adult progenitor cells (Mora- Lee et al 2012) in animal models of stroke have been reported with unanimous positive therapeutic results. Although mesenchymal stem cells were first identified four decades ago as adherent cells with fibroblastoid morphology being able to differentiate into cells of mesodermal origin such as osteocytes, chondrocytes, and adipocytes (Friedenstein et al 1974), they were later found to be also capable of differentiating into ectodermal and endodermal elements (Lakshmipathy and Verfaillie 2005;Ikegame et al 2011).…”
Section: Stem Cells: Their Natures Sources and Therapeutic Potentialsmentioning
confidence: 99%